ISLAMIC LAW AND SOCIAL UNITY IN A PLURAL SOCIETY AN INTEGRATIVE APPROACH BASED ON MAQĀṢID - Malik, Ridwan; Kurniati, Kurniati; Budiarti, Budiarti (Fakultas Syariah (Syari'ah Faculty ), 2025)
In a pluralistic Muslim society like Indonesia, Islamic law often faces challenges in fulfilling its integrative role amid religious, cultural, and ethnic diversity. This study aims to explore the potential of Islamic law as an integrative instrument in achieving social unity through the maqāṣid al-sharīʿah approach. The method employed is qualitative research based on library study, with a focus on content analysis of classical and contemporary texts, as well as legal documents and public policy. The findings reveal that maqāṣid al-sharīʿah provides a conceptual framework that enables Islamic law to function not only as a normative system but also as a contextual and inclusive public ethic. This approach promotes legal interpretations oriented toward public benefit (maṣlaḥah), substantive justice, and the protection of vulnerable groups. Moreover, the concepts of fiqh al-waqi’ and fiqh al-ta‘āyush have proven effective in bridging religious norms with social dynamics, particularly through forums such as FKUB and the active roles of religious and traditional leaders. The findings also show that education based on fiqh al-akhlāq al-ijtimāʿiyyah and public policies applying the principle of al-maṣlaḥah al-ʿāmmah can sustainably strengthen social cohesion. This study concludes that an integrative approach based on maqāṣid is a viable alternative solution for building social unity without sacrificing diversity.